Age Estimation with Cemental Incremental Lines in Normal And Periodontally Diseased Teeth Using Phase Contrast Microscope - Ameena Sultana; Heena Zainab; Pramod Jahagirdar; Deepa Hugar; Shaimaa (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Forensic age estimation defines an expertise in forensic medicine, which aimsto define in the most accurate way to determine the unknown chronological age of the personinvolved in judicial or legal proceedings. Dental cementum is a vital tissue which demonstratescontinuous apposition throughout the life of the tooth. Literature studies have revealed that toothcemental annulations(TCA) would serve as a reliable tool in establishing the age of an individual.The use of specialized microscopic methods are been employed to enhance the assessment ofthe cemental annulations. The study aims at assessment and evaluation of cemental annulationsin normal and periodontally diseased extracted teeth using phase contrast microscopic method.Methodology: A total of 60 teeth were included in the study and out of which thirty teeth were normaland 30 were periodontally involved teeth respectively. Longitudinal ground sections were prepared usingmicromotor and diamond disc. Sections were mounted and observed under phase contrast microscope.Measurements were made using an image analyzer software. The total width of cementum was dividedby the distance between two incremental lines. The eruption age of the tooth was then added to this toobtain the chronologic age for each individual. The results of the study showed no significant deviationof estimated age from the actual age in both periodontally sound and periodontally diseased teeth.Conclusion: The study concludes that the use of phase-contrast microscopy in conjunction with imageenhancement procedures improves the accuracy of age estimation and may serve as a reliable aid inforensic identification.